Urban agriculture: the role of knowledge among farmer in Malaysia - Zainal, Milah; Hamzah, Siti Raba'ah (Human Resource Management Academic Research Society, 2017)
Following the phenomenal increase in the cost of living in the city, the government is committed to guarantee the quality and food security of the population in the country. Accordingly, as a strategy for increasing food productivity there are a variety of methods, technologies and innovations that have been introduced. Urban agriculture is a practical approach among the urban population to produce their own food defined as all activities done related to agriculture and agricultural activities in the urban area. It can reduce daily expenses due to the rise in cost of living in the city. However, the acceptance of urban agriculture among farmers in the city was influence by their level of cognitive, affective and behavioral. Thus, this study aims to know the important knowledge regarding urban agriculture activities among farmers in Malaysia for future development strategy.